Long-Term Outcomes After Percutaneous Transluminal Pulmonary Angioplasty in Patients With Takayasu Arteritis and Pulmonary Hypertension - Huang, Zhiwei; Wang, Man; Hu, Fenghuan; Liu, Xiaoning (Frontiers in Immunology, 2022)
Objective To investigate the long-term efficacy of percutaneous transluminal pulmonary angioplasty (PTPA) in patients with Takayasu arteritis (TA) and pulmonary artery stenosis and pulmonary hypertension (PH). Methods Data from 183 lesions from 79 surgeries performed on 32 patients with TA and PH were analyzed. Symptoms, laboratory investigation results, World Health Organization (WHO) functional class, 6-min walk distance (6 MWD), hemodynamic parameters, and prognosis were analyzed at baseline and follow-up. Results The mean (± SD) age of the 32 patients (28 female, 4 male) was 42.8 ± 11.9 years, and the median follow-up was 49.5 months (interquartile range, 26–71 months). Compared with baseline, changes in total bilirubin, N-terminal pro-brain natriuretic peptide (NT-proBNP) level, 6 MWD, and WHO score functional class demonstrated significant differences (P<0.001). Echocardiography findings, right and left ventricular diameter, tricuspid annular plane systolic excursion, and estimated pulmonary artery systolic pressure were all improved (P=0.016, P<0.001, P<0.001, and P=0.005, respectively). Importantly, repeat right heart catheterization revealed that mean pulmonary artery pressure, pulmonary vascular resistance, and cardiac index also improved significantly at follow-up (P<0.001, P<0.001, and P=0.011, respectively). Pulmonary angiography revealed post-procedure restenosis in 64 (35.0%) lesions underwent PTPA within three to six months. Among three patients who underwent stent implantation, one experienced restenosis. Two patients died during the follow-up period, one from aggravation of right heart failure after lung infection, and the other in a traffic accident. Conclusions Results of this study indicated that PTPA significantly improved clinical symptoms, exercise tolerance, and hemodynamic parameters in patients with TA pulmonary artery stenosis and PH. More importantly, reperfusion pulmonary edema significantly decreased, and no patient died of PTPA-related complications with guidance from the pressure wire.